Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1097/nmd.0000000000001092
|View full text |Cite
|
Sign up to set email alerts
|

Dual Diagnosis and Application Problems in the Use of the Construct

Abstract: Dual diagnosis (DD) commonly identifies a condition of co-occurrence of substance use disorders and psychological or psychiatric disorders. Many scholars have tried to explain this phenomenon, yet no agreement has been found: methodologies of intervention and treatment are numerous, but there is no uniformity of methodology. Our work aims to search critical aspects linked to this fragmented framework, to facilitate those who use the construct of DD. We have elaborated a literary review focused on specific crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…To date, literature has discussed the definition and relevance of dual diagnosis, the inclusion of knowledge and guidance from the lived experience perspective (Iudici et al , 2020) and attitudes to working with people living with dual diagnosis (Foster, 2020; Marel et al , 2016; Petrakis, 2018). Other papers include government leadership, system design and the development and evaluation of integrated treatment models (Department of Health and Human Services, 2007; Mueser et al , 2003; Deady et al , 2014; Fantuzzi and Mezzina, 2020).…”
Section: Dual Diagnosis Integrated Treatment – Literature Reviewmentioning
confidence: 99%
“…To date, literature has discussed the definition and relevance of dual diagnosis, the inclusion of knowledge and guidance from the lived experience perspective (Iudici et al , 2020) and attitudes to working with people living with dual diagnosis (Foster, 2020; Marel et al , 2016; Petrakis, 2018). Other papers include government leadership, system design and the development and evaluation of integrated treatment models (Department of Health and Human Services, 2007; Mueser et al , 2003; Deady et al , 2014; Fantuzzi and Mezzina, 2020).…”
Section: Dual Diagnosis Integrated Treatment – Literature Reviewmentioning
confidence: 99%
“…This study uses an interactionist epistemological theory framework (Iudici et al, 2020;Salvini, 1998;Salvini and Dondoni, 2011). From this perspective, thought processes and meanings are shaped by the social interactions surrounding an individual, and discourses form a structural sequence of intentional acts (Blumer, 1969;Harr e and Gillett, 1994;Iudici and Fabbri, 2017;Iudici et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, the incidence of a diagnosed mental disorder along with a co-occurring substance use disorder (SUD) in the same person, referred to as dual diagnosis (DD), has become a well-established and evolving field of research (Iudici et al 2020 ; Morisano, Babor & Robaina 2014 ; Vitali et al 2018 ). Recent findings found that up to 75% of patients with a severe mental illness have also been diagnosed with an SUD, while 60% of adult patients with an SUD were found to be diagnosed with at least one severe mental illness (Temmingh et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The DSM-V utilises a categorical approach but proposes a “dimensional” approach that allows for a more flexible understanding of DD that attempts to accommodate the subjectivity of each patient and has the potential to improve the clinical practice and diagnostic accuracy (Vitali et al 2018 ). However, due to the high prevalence of this psychiatric presentation, standardised diagnostic criteria need to be developed and added to newer editions of the DSM to assist clinicians in the effective and timely diagnosis and treatment of DD patients (Iudici et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation